Misspelled Words in The Netflix Series "Baby Reindeer" and Speech Act Implications in Understanding Their Meanings - Nabilla, Adha; Salim Mansyur, Agus; Nurhapitudin, Irman (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
This research aims to analyze what language mistakes exist in emails sent by one of the characters in the Netflix series Baby Reindeer and how meaning can be interpreted through such mistakes. Qualitative method is used in this study because this research is conducted by understanding and processing meaning through writing and images. In addition, this method is used because the results of this research are in the form of writings and not images. Through analysis using surface strategy taxonomy, 91 misspelled words were found in 32 sent emails. There are 37 words in omission type, 18 words in addition type, 27 words in misformation type, and 9 words in misordering type. This research also uses Yule's speech act theory to analyze the meaning of the sentences or emails. This research is expected to provide new knowledge in detecting an error that can produce differences in meaning and changes from the original meaning to the meaning interpreted by the audience. In addition, the writer also hopes that this study is useful for future writers who want to focus their research on linguistics aspects.